Rancang Bangun Sistem Informasi Pemantauan Perkembangan Mitra Binaan pada Pelindo III Cabang Benoa Bali - Sabatini, Erwin Pramastya; Widodo, Arifin Puji; Wurijanto, Tutut (Jurnal JSIKA, 2014)
The problem in PKBL activity of benoa port is based on PKBLs loan report in 2011, there is 100% total bad debt with the details 15 bad debt of 15 loans. and from the PKBLs loan report in first semester 2012, there is 87% total bad debt with the details 26 bad debt of 30 loans. the percentages amount of bad debt is caused by mitra could not adequate to pay their loan. PKBLs officer difficult to monitor when partner could not settle their loan. In order to solve the problem, they need monitoring information system of fostered partner which give benefit to monitor financial condition of fostered partner. system will monitor with liquidity factor, solvency and profitability With the monitoring information system of fostered partner, PKBLs officer obtain the information about partners result of paying ability asessment, information about partners result of financial eficiency assessment and information about partners result of determination founding assessment.